2009
DOI: 10.1111/j.1365-2036.2009.04064.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: lansoprazole 15 or 30 mg once daily vs. placebo for treatment of frequent nighttime heartburn in self‐treating subjects

Abstract: SUMMARY BackgroundFrequent nighttime heartburn is common. Lansoprazole 15 mg is indicated for treatment of heartburn and other gastro-oesophageal reflux disease-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Subjects treated with lansoprazole also experienced a higher mean percentage of nighttimes with no heartburn during the 14-day treatment period, compared with subjects on placebo (p<0.0001 for all doses vs placebo) (Figure 3) [41]. The results from these studies show that, compared with placebo, lansoprazole 15 mg and 30 mg are both efficacious for the treatment of frequent heartburn.…”
Section: Lansoprazole In the Treatment Of Acid-related Gastrointestinmentioning
confidence: 83%
See 4 more Smart Citations
“…Subjects treated with lansoprazole also experienced a higher mean percentage of nighttimes with no heartburn during the 14-day treatment period, compared with subjects on placebo (p<0.0001 for all doses vs placebo) (Figure 3) [41]. The results from these studies show that, compared with placebo, lansoprazole 15 mg and 30 mg are both efficacious for the treatment of frequent heartburn.…”
Section: Lansoprazole In the Treatment Of Acid-related Gastrointestinmentioning
confidence: 83%
“…Results from three studies described demonstrated that oncedaily lansoprazole 15 mg was effective and had a good tolerability profile in the treatment of frequent, including nighttime, heartburn in a self-treating population. [40,41] The 15-mg dose of lansoprazole, the lowest effective dose for acid-related gastrointestinal disorder symptoms, was shown to be as effective as the 30-mg dose. [41].…”
Section: Place Of Lansoprazole In the Management Of Heartburnmentioning
confidence: 99%
See 3 more Smart Citations